Processed Aortic Allografts for Oesophagoplasty in Dogs - Balagopalan T P (Department of Surgery, College of Veterinary and Animal Sciences, 1998)
The study was conducted with the objectives of a. Preparation, preservation and evaluation of chrome/ glutaraldehyde cross linked aortic tissue of dogs and to compare the relative acceptability and efficacy of them for cervical oesophagoplasty in dogs, and b. Evaluation of modified pharyngostomy feeding method and its effect on healing at cervical oesophagoplasty site in dogs. The experiment was conducted in thirty, apparently healthy, adult, nondescript dogs of either sex weighing 9-13 kg. The animals were randomly divided into three groups viz., group I, II and III. Group II and III were subdivided into two subgroups each, namely IIA, IIB and IIIA, IIIB. Group I and the subgroups consisted of six animals each. Animals of group I were subjected to sham operation. Cervical oesophagoplasty using chrome processed aortic allograft and glutaraldehyde processed aortic allograft were performed in animals of group II and III respectively. Pharyngostomy tube feeding was instituted in three animals of group I and all animals of subgroups IIB and IIIB.